PENGARUH PEMAHAMAN PERATURAN PAJAK, SOSIALISASI PAJAK, DAN TINGKAT KEPERCAYAAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM (Survey Pada Pedagang Batik di Pasar Klewer Surakarta) - Eka Puspita Handayani; Fadjar Harimurti; Djoko Kristanto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Taxes are a source of state income which is essential for the implementation and enhancement of national development to achieve the prosperity and welfare of the community. The purpose of the study is to know (1) influence of understanding of tax regulations on SMES taxpayer compliance (2) influence of tax socialization on MSME taxpayer compliance (3) Influence of confidence level against taxpayer compliance Umkm. This research uses primary data in the form of questionnaire given to the respondents who are batik traders in Pasar Klewer Surakarta. The population in this research is a total of 508 businessmen. With samples of 50 batik merchants. The sampling technique in this study is Simple Ramdom Sampling. The analytical techniques used in this study are the techniques of multiple linear regression analyses. Based on the data analysis of tax socialization influence and the level of confidence on the taxpayer compliance of SMES obtained positive and significant results. While the influence of understanding tax regulation on MSME taxpayer compliance obtained no significant effect.